Evaluation of Glymphatic System Using Diffusion MR Technique in T2DM Cases - Yang, Guangwei; Deng, Nan; Liu, Yi; Gu, Yingjiang; Yao, Xiang (Frontiers in Human Neuroscience, 2020)
Abstract Objective: We aimed to evaluate the activity of the human glymphatic system in type 2 diabetes mellitus (T2DM) using diffusion tensor image analysis along the perivascular space (DTI-ALPS). Methods: Diffusion tensor images were acquired to calculate the diffusivities in the direction of the x-axis (right-to-left) (Dx), y-axis (anterior-to-posterior) (Dy), and z-axis (inferior-to-superior) (Dz) of the plane of the lateral ventricle body in 20 patients with type 2 diabetes and 10 people in a control group. We evaluated the diffusivity along the perivascular spaces, as well as the projection fibers and association fibers, separately. The analysis along the perivascular space (ALPS-index) was defined as the mean (Dxpro, Dypro)/mean (Dypro, Dzasc), where the Dxpro and Dxasc were the Dx values in the projection and association fiber areas, respectively. Results: There were significant differences in diffusivity along the projection fibers and the association fibers among the groups. The significant differences among the groups along the perivascular spaces, shown as the ALPS-index and a medical history of T2DM, indicating lower water diffusivity along the perivascular space in relation to type 2 diabetes severity, was also observed. Conclusion: Lower diffusivity along the perivascular space on DTI-APLS can reflect impairment of the glymphatic system in T2DM. This study showed that the activity of the glymphatic system could be evaluated by diffusion tensor images analysis.